2021
DOI: 10.1177/03611981211019732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impacts of Speed Limit Increases on Rural Two-Lane Highways Using Quantile Regression

Abstract: Understanding speed selection behavior of drivers following speed limit increases is critically important. To date, the literature has largely focused on freeways and the effects of speed limit changes on two-lane highways remains under researched. Prior research has generally focused on changes to mean speeds, although the speeds of both the highest and lowest drivers are also of great interest. This study investigates trends in free-flow travel speeds following 2017 legislation that increased the posted spee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…or 18-in. display) to be effective in speed reduction in other contexts such as interchange ramps and rural highway curves ( 5 , 18 ). To that end, future evaluations should also assess the amount of time that the portable DSFS, such as those utilized in this study, should be left on site before moving elsewhere.…”
Section: Summary Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…or 18-in. display) to be effective in speed reduction in other contexts such as interchange ramps and rural highway curves ( 5 , 18 ). To that end, future evaluations should also assess the amount of time that the portable DSFS, such as those utilized in this study, should be left on site before moving elsewhere.…”
Section: Summary Conclusion and Recommendationsmentioning
confidence: 99%
“…This includes Michigan, where, in 2017, speed limits were increased from 55 to 65 mph on greater than 900 mi of rural state highways across the northern portions of the state. Recent research found that travel speeds increased by 2.8 to 4.8 mph in a sample of rural highway segments where the speed limit was raised to 65 mph ( 18 ). However, this prior research did not consider impacts to travel speeds within speed transition zones along those routes.…”
mentioning
confidence: 99%
“…A recent safety evaluation of freeway exit ramps also found crashes to increase as the speed difference between mainline and ramp speed increased ( 9 ). This speed difference is expected to increase with the trend of increasing speed limits, which often results in an increase in average speed, and an even higher increase in speed by the faster drivers ( 10 , 11 ).…”
mentioning
confidence: 99%
“…This includes Michigan where, in 2017, speed limits were increased from 55 to 65 mph on more than 900 mi of rural state highways across the northern portions of the state ( 22 , 23 ). Recent research found that travel speeds increased by 2.8 to 4.8 mph along a sample of rural highway segments where the speed limit was raised from 55 to 65 mph ( 24 ). However, prior research has not explicitly considered the impact on travel speeds on curved portions of highway segments, where safety performance issues may be particularly exacerbated by increased travel speeds.…”
mentioning
confidence: 99%